2010
DOI: 10.1002/jcu.20757
|View full text |Cite
|
Sign up to set email alerts
|

Four‐dimensional and Doppler sonography in the diagnosis and surveillance of a true cord knot

Abstract: Prenatal diagnosis of a true knot of the umbilical cord is often an incidental observation at ultrasound with a difficult differential diagnosis between true and false knots. Furthermore, little is known about the optimal management of these cases. We report the importance of color Doppler and four-dimensional ultrasound for the differential diagnosis in the case of true cord knot and the role of Doppler flow velocimetry in the management of that case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Subsequently, three-dimensional ultrasound has enabled precise depiction of a true knot of the umbilical cord ( Figures 5, 6, 7). [67][68][69][70][71][72][73][74][75][76] Notwithstanding the Figure 4 Power Doppler image depicting a true knot of the umbilical cord. Note the "smiley face" features (almost complete circle of umbilical cord [face outline] surrounding "eyes" and "mouth/smile"), representing the en-face presenting two umbilical arteries and umbilical vein, respectively.…”
Section: True Knot(s) Of the Umbilical Cordmentioning
confidence: 99%
“…Subsequently, three-dimensional ultrasound has enabled precise depiction of a true knot of the umbilical cord ( Figures 5, 6, 7). [67][68][69][70][71][72][73][74][75][76] Notwithstanding the Figure 4 Power Doppler image depicting a true knot of the umbilical cord. Note the "smiley face" features (almost complete circle of umbilical cord [face outline] surrounding "eyes" and "mouth/smile"), representing the en-face presenting two umbilical arteries and umbilical vein, respectively.…”
Section: True Knot(s) Of the Umbilical Cordmentioning
confidence: 99%
“…However, Marco Scioscia et al suggested 4-dimensional and color Doppler sonography as a diagnostic modality in this regard. 12 This case was a neonate who had an uneventful prenatal, perinatal, and postnatal course, despite having two true knots in the navel string. However, in two other similar cases, published in 1998 13 and 2017, 14 both embryos experienced IUGR and the fact that their umbilical cords showed two true knots is believed to be the probable cause of this situation.…”
Section: Discussionmentioning
confidence: 99%
“…The true knots are identified with increased tension and thus with a higher risk for obstetric and neonatal outcome intervention. The loose knots can tighten during pregnancy due to fetal movements, or during labor, leading to decreased flow in the cord blood [11]. The true knot of the umbilical cord has a relatively high incidence at birth [6,12].…”
Section: Classification and Epidemiologymentioning
confidence: 99%
“…Usually the true knot of umbilical cord is presented as an unexpected discovery at delivery and there is no increased risk to obstetric intervention or worsening in neonatal outcomes because most of them are loose [12]. On the other hand, the loose knot can tighten during pregnancy due to fetal movements or during delivery, leading to decreased blood flow through umbilical cord and consequent fetal distress, asphyxia and death [5][6][7]11]. This would happen especially after rigorous fetal movements.…”
Section: Pathophysiologymentioning
confidence: 99%